Foreign Experience of Libraries Communication Policy: Current Practice and New Challenges - Symonenko Olena (Наукові праці Національної бібліотеки України імені В.І. Вернадського, 2020)

(untitled)
The article examines modern practices of communication processes in foreign libraries. The directions of transformation of libraries as a public institute based on the system of digital information communications are considered. The article illustrates how libraries can contribute to a more effective policy of state authorities. The potential of foreign libraries in the political communication system is outlined. Attention is drawn to the fact that since libraries are those organizations that enjoy a high level of trust among community members, public discussions, especially in the premises of libraries, will increase public confidence in authorities and create more effective communication. The analysis of new forms of libraries work in the world makes it possible to conclude that for public authorities, libraries serve as an effective channel of information exchange, which allows to establish a trusting dialogue with citizens and to have feedback, to increase the level of citizens’ trust in the authorities. Therefore, foreign libraries are authorities partners, meeting their information needs and provi- ding the public with official and socially important information. In conclusion, it should be noted that the world library community is now actively seeking new ideas, forms and methods of work, innovating in order to be in demand. This experience from around the world can be a useful source of ideas and initiatives for many libraries. It is concluded that interaction between the public and state authorities is a priority in foreign libraries activity.